A qualitative investigation into the HIV disclosure process within an intimate partnership: 'The moment I realized that our relationship was developing into something serious, I just had to tell him'. Issue 1 (2nd December 2016) - Smith, Charlotte; Cook, Rachel; Rohleder, Poul
Abstract : Objectives: This study sought to elucidate the process through which people living with HIV (PLWH) in the United Kingdom disclose their status to an intimate partner (IP). Design: A qualitative cross‐sectional survey design was used. Method: A total of 95 PLWH took part. They were presented with a series of open‐ended questions enquiring into their last experience of disclosing to an IP. The data were analysed using thematic analysis. Results: Disclosure became a salient issue when the discloser acknowledged their relationship as meaningful. A decision to tell was mostly made to build a foundation for the evolving relationship. Once the decision was made, it was enacted via one of two mechanisms (self‐initiated or opportunistic) and partners' reported reactions fell within one of four main reaction types. In the long‐term for couples who remained together, disclosure was understood to have brought them closer. However, for both those whose relationships remained intact, and for those whose relationship had since broken down, sexual difficulties associated with being in a sero‐discordant partnership pervaded. At a personal level, the experience resulted in increased confidence in living with the diagnosis, and an increased sense of disclosure mastery. Conclusions: Disclosure is a highly nuanced process. In particular, it was found to be largely characterized by the IP relational context in which it was occurring. The clinical and theoretical implications of these findings are discussed. In particular, these findings highlight a need for the provision of long‐term support to PLWH in negotiating their relationships throughout the process. Statement of contribution What is already known on this subject? Disclosing a HIV+ status to an intimate partner (IP) is key in addressing the global HIV epidemic, social stigma, and the psychological and physical well‐being of people living with the condition. It is increasingly recognized that HIV disclosure is a process, rather than an event. Researchers have begun to initiate a line of research into a process‐based theoretical account of disclosure. What does this study add? This study provided a nuanced account of the disclosure process within an IP relationship. The process was found to be largely influenced by the discloser's subjective experience of the intimate partnership. The findings point to a need for a disclosure intervention that supports couples more longitudinally, particularly in negotiating the emotional and sexual difficulties that often arise upon disclosing.